OVERCONFIDENCE BIAS IN INVESTMENT DECISIONS ON INDONESIAN STOCK MARKET - Wijoyo, Fanny; Arifin, Agus Zainul (International Journal of Application on Economics and Business, 2024)
The investor’s growth on the Indonesian Stock Exchange for the period 2020 to January 2023 is quite significant. However, this growth was accompanied by a tendency towards overconfident bias. This behavior’s increase errors in investment decision making: increasing risk and reducing returns. The aim of this research is to verify the relationship between neuroticism, conscientiousness, and openness traits on the overconfidence behavioral bias to stock investors using The Big Five Personality approach. The research uses primary data on stock investors in Indonesia with total 483 respondent. Data analysis method used the SEM-PLS version 4.0. The research results prove that neuroticism and conscientiousness traits have a positive effect on overconfidence bias. Other evidence shows, that openness has a negative effect on overconfidence bias. This evidence applies to both male and female investors.